The Influence of Reward, Work Environment, and Motivation on Employee Performance in The EKP Department of FEB Universitas Negeri Malang - Akbar, M. Taufik; Imron, Moh.; Syafuddin, Amin (Universitas Negeri Gorontalo, 2025)
Purpose: AThe purpose of this study is to explore how different factors, specifically reward, work environment, and motivation, impact employee performance within the EKP Department of FEB Universitas Negeri Malang. Organizations rely heavily on human resources to achieve their goals, and effective management of these resources is crucial for sustained success. Understanding the relationship between these factors and employee performance can help managers create an environment that supports high performance and satisfaction. Employee performance is influenced by both internal and external factors. Rewards, which can be both intrinsic and extrinsic, serve as a form of recognition for employees’ efforts and achievements. Meanwhile, the work environment encompasses the physical, psychological, and social conditions in which employees work. Motivation drives employees to put forth their best efforts, and it can be fostered through various means, including recognition, support, and personal growth opportunities. By examining how reward, work environment, and motivation contribute to employee performance, this study aims to provide insights that can guide organizational strategies. Identifying the most influential factor among these three can help managers and decision-makers prioritize interventions and resources to improve employee productivity and overall organizational effectiveness.Design/Methodology/Approach: This research uses a quantitative approach with a saturated sampling technique, involving all 47 employees of the department. Data was collected using questionnaires that applied a five-point Likert scale to measure the perceptions of respondents on each factor. Before performing multiple regression analysis, classical assumption tests were conducted to ensure data validity, addressing issues such as normality, multicollinearity, and heteroscedasticity. The use of multiple regression was justified despite the small sample size because it allowed for analyzing the simultaneous and individual influence of the independent variables on employee performance.Findings: The findings indicate that reward, work environment, and motivation all significantly influence employee performance, both individually (partially) and together (simultaneously). Of these three factors, the work environment was found to have the strongest impact on employee performance. This suggests that creating a supportive, well-organized, and comfortable work environment is crucial for enhancing employee productivity. The study highlights the practical importance of focusing on both tangible and intangible aspects of the work environment, as well as implementing fair reward systems and motivational strategies, to support high employee performance.